Evaluation of a new clinical performance assessment tool : A reliability study - C. Joseph; J. Frantz; C. Hendricks; M. Smith (South African Journal of Physiotherapy, 2012)
Clinical practice is an essential requirement of any graduatephysiotherapy programme. For this purpose, valid and reliable assessment toolsare paramount for the measurement of key competencies in the real-worldsetting. This study aims to determine the internal consistency and inter-raterreliability of a newly developed and validated clinical performance assessmentform. A cross-sectional quantitative research design was used, which includedpaired evaluations of 32 (17 treatment and 15 assessment) student examinationsperformed by two independent clinical educators. Chronbachs alpha was computedto assess internal consistency and intraclass correlation coefficient (ICC’s) withconfidence intervals of 95% were computed to determine the percentage agreement between paired examiners. Thedegree of internal consistency was substantial for all key performance areas of both examinations, except for timeand organisational management (0.21) and professionalism (0.42) in the treatment and evaluation examinationsrespectively. The overall internal consistency was 0.89 and 0.73 for both treatment and assessment examinations,indicating substantial agreement. With regard to agreement between raters, the ICC’s for the overall marks were0.90 and 0.97 for both treatment and assessment examinations. Clinical educators demonstrated a high level ofreliability in the assessment of students’ competence using the newly developed clinical performance assessment form.These findings greatly underscore the reliability of results obtained through observation of student examinations, andadd another tool to the basket of ensuring quality assurance in physiotherapy clinical practice assessment.